A coordination environment effect of single-atom catalysts on their nitrogen reduction reaction performance. Issue 31 (1st August 2022) - Han, Miaomiao; Huang, Youjie; Zhang, Haimin
Abstract : O in coordination was found to have a positive effect on the activation of N2, but a negative effect on the stability, while N is the other way around. The coexistence of N and C in coordination leads to a good performance of Fe–N2 C2 –C. Abstract : Understanding the structure–activity relationship of an active site is of great significance toward the rational design of highly active catalysts. In this study, we have performed density functional theory calculations to investigate the coordination environment effect of Fe-, N-, and O-doped carbon on their nitrogen reduction reaction (NRR) properties. Our results indicate that the presence of O atoms in the coordination environment favors the activation of N2 molecules but is unfavorable to the stability, while the existence of N will weaken the adsorption of N2 and increase the reaction barrier of the first hydrogenation step. Fe–C4 –C has the lowest potential for activating N2 . A compromise is Fe–N x C4− x –C, where the interaction of C and N in coordination regulates the spin polarization of Fe and thus the 3d states around the Fermi level. Fe–N2 C2 –C was found to be the best one and NRR can proceed via the distal and alternative reaction pathways with the first hydrogenation step of N2 being the potential-limiting step and the Gibbs free energy change (Δ G ) being 0.75 eV.